2010
DOI: 10.1007/s12630-010-9375-4
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Acute kidney injury in critical illness

Abstract: Purpose This review provides a focused and comprehensive update on emerging evidence related to acute kidney injury (AKI).Principal findings Acute kidney injury is a significant clinical problem that increasingly complicates the course of hospitalization and portends worse clinical outcome for sick hospitalized patients. The recent introduction of consensus criteria for the diagnosis of AKI (i.e., RIFLE/AKIN classification) have greatly improved our capacity not only to standardize the diagnosis and classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 117 publications
2
43
0
3
Order By: Relevance
“…Urinary clusterin, a marker for AKI that correlates with hypoxic tubular damage (28), and kidney injury molecule-1 (KIM-1), a glycoprotein released in the event of early proximal tubule injury (6,59,61), both increased significantly after RM ( Fig. 2A and 2B).…”
Section: Urinary and Plasma Markers Of Akimentioning
confidence: 99%
“…Urinary clusterin, a marker for AKI that correlates with hypoxic tubular damage (28), and kidney injury molecule-1 (KIM-1), a glycoprotein released in the event of early proximal tubule injury (6,59,61), both increased significantly after RM ( Fig. 2A and 2B).…”
Section: Urinary and Plasma Markers Of Akimentioning
confidence: 99%
“…In particular, there has been a transition in patient demographics such that patients are older and have a greater burden of comorbid disease. These patients are more likely developing AKI in the context of multiple organ failure (7). The commonest cause of AKI in the present study was sepsis related AKI (35%) followed by malaria (14%) and gastrointestinal problems (13%) such as diarrhea; persistent vomiting and upper GI bleed.…”
Section: Malleshappa P Et Al : Spectrum Of Acute Kidney Injury and Itmentioning
confidence: 59%
“…However, a prospective randomized study in a mixed ICU population found no difference in survival between early (on average within 7 hours of development of AKI) and late (on average 42 hours There is a strong relationship between severity of AKI and mortality (4). Indeed, even after adjustment for relevant covariates, several epidemiologic studies have shown the presence and severity of AKI to independently portend higher risk of death (7). A number of epidemiologic studies have tried to quantify the performance of the RIFLE classification with receiver operator characteristic curves (21,22).…”
Section: Malleshappa P Et Al : Spectrum Of Acute Kidney Injury and Itmentioning
confidence: 99%
“…Complications included a composite of major cardiovascular events, pneumonia, bacteremia, acute kidney injury (AKI), wound infection, and in-hospital mortality. ICD-9 codes were used to determining the presence of complications for all of these except for acute kidney injury, which was defined as an increase in serum creatinine greater than 50% from the patient's baseline admission creatinine (Bagshaw et al, 2010).…”
Section: Methodsmentioning
confidence: 99%